SYNTHESIS OF NAFEO2 FROM FECL3 AND NA2CO3 TECHNICAL GRADE FOR CATHODES IN SODIUM ION BATTERIES THROUGH WET MILLING METHOD WITH ETHYLENE GLYCOL MEDIATED - Taufik, Dede
Sodium ion batteries have a similar working system to lithium ion and consist of a cathode, anode and a separator in an electrolyte medium. The cathode is a limiting factor in battery performance but determines the capacity, stability, safety and cost of producing ion batteries. Therefore, many studies have studied about the cathode. The type of O3/P2-based transition metal oxide layer was chosen because it has a high theoretical energy capacity and is easy to produce. This type of cathode is written in the form of Nax(TM)O2 where TM is a transition metal such as Ti, V, Cr, Ni, Mn, Fe and Co. NaFeO2 has an O3 type layered structure consisting of abundant raw materials and its structure is a reference for the synthesis of other compounds. Much has been done by previous researchers but still uses materials with high purity so they are still relatively expensive to produce. In this research, NaFeO2 has been synthesized using technical FeCl3 as Fe precursor and technical Na2CO3 as Na precursor. FeCl3 is dissolved in water and then precipitated with ammonia. The precipitate was dried for 24 hours to dry and then mixed by wet grinding with soda ash in ethylene glycol medium. The milling results were tested for TG/DTA and then calcined at temperatures of 475, 575, 650 and 700oC. The powder was analyzed for mineralogy (XRD), morphology and microstructure (TEM/SEM-EDS), then coated on aluminum foil and assembled into a battery cell using hardcarbon as an anode. XRD data from samples calcined at a temperature of 475 oC contain magnetite and soda ash phases, while at temperatures of 575, 650, 700oC the phases are Fe3O4, ?-NaFeO2, and ?-NaFeO2. The difference in calcination temperature from 575–700oC did not change the chemical composition, but increased the concentration of the ?-NaFeO2 phase and decreased the concentration of the Fe3O4 and ?-NaFeO2 phases. The samples were calcined at 575 and 650oC, forming nanorods with an average length of ~260 nm and an average diameter of ~72 nm. At 700oC calcined samples agglomerate and it is difficult to determine the size. The battery performance characterization from EIS and CV showed that the sample with the largest -NaFeO2 phase content (NFO 575) have the highest conductivity and coeffient difusion were 1.38 x 10 -4 S/cm and 1.02 x 10-8 cm2/s with an output current was 17 mA.